Macroscopic-Scale Template Synthesis of Robust Carbonaceous Nanofiber Hydrogels and Aerogels and Their Applications - Liang, Hai-Wei; Guan, Qing-Fang; Chen, Li-Feng; Zhu, Zhu; Zhang, Wen-Jun; Yu, Shu-Hong (Angewandte Chemie International Edition, 2012)
Robust nanofiber gels: Monolithic hydrogels and aerogels consisting of uniform carbonaceous nanofibers (CNFs) were fabricated on a macroscopic scale (12 L, see picture) by a simple template‐directed, hydrothermal carbonization process. The high surface reactivity of the CNFs and high porosity and robust nature of the gels can be exploited in applications such as selective adsorbents and templates for creating functional composite gels.